PROFESIONALISME TENAGA KEPENDIDIKAN - Ibrahim Ibrahim; Nisbatul Imaroh; Kris Setyaningsih (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This research discusses the Professionalism of Education Personnel (Tata Usaha) at MTs Al-Muhajirin Sumber Makmur, Kec. Muara Padang Banyuasin Regency, South Sumatra Province. In this study, researchers used qualitative descriptive research. The techniques used in data analysis are data reduction, data presentation, and inference. The results showed that the professionalism of education personnel (administrative) in MTs Al-Muhajirin can be said to be quite good in terms of personality and social competence, namely judging from the attitude, behavior, discipline and responsibility of education personnel during the administrative service process for students. But in terms of technical and managerial competence is not good enough, because in technical problems education personnel do not master the field.